Design, synthesis and characterization of polysiloxane and polyetherdiamine based comb-shaped hybrid solid polymer electrolytes for applications in electrochemical devices. (January 2019) - Deka, Juti Rani; Saikia, Diganta; Lou, Gwo-Wei; Lin, Chien-Hua; Fang, Jason; Yang, Yung-Chin; Kao, Hsien-Ming
Graphical abstract: Highlights: Polysiloxane based SPEs are synthesized by hydrosilylation and sol-gel reactions. DSC reveals phase transformation of SPEs from semi-crystalline to amorphous structure. Maximum conductivity of 5.8 × 10 −4 Scm −1 at 80 °C is found for SPE with [O]/[Li] = 16. The SPEs exhibit an electrochemical stability window up to 4.8 V. Fabricated electrochromic device exhibits maximum electrochromic contrast of 49.3%. Abstract: In this study, polysiloxane and polyetherdiamine based comb-shaped solid polymer electrolytes (SPEs) are developed by hydrosilylation and sol-gel reactions of polymethylhydrosiloxane, allyltriethoxysilane, bis(2-aminopropyl) polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol and (3-glycidoxypropyl)trimethoxysilane followed by LiClO4 doping. The absence of residual Si‒H functionality in FTIR and 29 Si CPMAS NMR spectra confirms the completion of hydrosilylation reaction. The formation of comb-shaped SPEs with silicate backbones is confirmed by 13 C and 29 Si solid-state NMR spectroscopy. The maximum ionic conductivity value of 5.8 × 10 −4 S cm −1 is obtained for the SPE with [O]/[Li] ratio of 16 at 80 °C with electrochemical stability window reaching up to 4.8 V. The fabricated electrochromic device with the hybrid SPE of [O]/[Li] = 16 demonstrates good electrochromic contrast and optical density change values of 49.3% and 0.39, respectively, at wavelength of 550 nm. The results show that the present comb-shaped SPEs have potential to be used in various electrochemical devices.